2020
DOI: 10.4236/ojf.2020.101002
|View full text |Cite
|
Sign up to set email alerts
|

Using Water Stable Isotopes to Trace Water Sources of Three Typical Japanese Tree Species under Heavy Rainfall Conditions

Abstract: Stable isotopes of xylem water ( 18 O and D) have been successfully used to determine sources of soil water for plant transpiration, but mainly in drought-prone environments. The water uptake strategies of three representative tree species in Japan, namely cedar (Cryptomeria japonica), larch (Larix kaempferi) and beech (Fagus crenata), were investigated using δ 18 O and δD of water (precipitation, soil and xylem), together with wood α-cellulose δ 13 C and δ 18 O, along one growing season. The study was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Our results revealed that winter precipitation had positive as well as negative impacts on forests in north-eastern Japan. On the one hand, water saturated soils due to infiltration of water from rain-on-snow or snowmelt events (Hardy et al, 2001) supply plants sufficient moisture for transpiration in spring (Lopez Caceres et al, 2015;Osonoi, 2018;Schwartz & Karl, 1990, Zhang et al, 2020. Melting processes in spring last longer in forested areas than in clear cut sites, resulting in longer snow cover (Harpold et al, 2015;Jost et al, 2012).…”
Section: Possible Effects On Forestsmentioning
confidence: 99%
“…Our results revealed that winter precipitation had positive as well as negative impacts on forests in north-eastern Japan. On the one hand, water saturated soils due to infiltration of water from rain-on-snow or snowmelt events (Hardy et al, 2001) supply plants sufficient moisture for transpiration in spring (Lopez Caceres et al, 2015;Osonoi, 2018;Schwartz & Karl, 1990, Zhang et al, 2020. Melting processes in spring last longer in forested areas than in clear cut sites, resulting in longer snow cover (Harpold et al, 2015;Jost et al, 2012).…”
Section: Possible Effects On Forestsmentioning
confidence: 99%